G276(P) Paediatric journals: What do we want and can we get it?. (7th April 2014) - Spaull, R; Hayden, H; Chatterjee, S; Peek, R
Abstract : Aims: Doctors are obliged to keep up to date and take part in quality improvement activities (GMC, Duties of a Doctor). This requires critical appraisal of new research findings and translation into clinical practice. We investigated trainee access to medical journals across a UK deanery. Our aims were to assess use of journals throughout training; to explore perceived and desired journal access; and to correlate this with actual journal availability across training units. Methods: We surveyed paediatric speciality trainees across a UK deanery using a focussed online questionnaire. We asked how often trainees accessed published research for various purposes, how they accessed the literature, and if they had access to 10 relevant paediatric journals. We contacted trust libraries to ascertain what access was available across the deanery. Results: We received 40 responses from trainees at all stages of the programme and from all trusts within the deanery. Trainees access journals weekly to monthly for patient care and personal learning or development; more senior trainees accessed journals more often, there was no difference between secondary and tertiary units. Comparison of perceived versus actual access revealed a lack of awareness of library resources (42% were unaware of access to Paediatrics despite being available in all 8 trusts). Trainees identified a broad range of tools used to access articles. Only 35% identified the hospital library: Conclusion: Most trainees access medical journals on a regular basis for personal learning, patient care, audit and research. Perceived access to journals did not match library resources, but access provided by trusts is often not in the format trainees desire. Several respondents described ideal access as being online and available remotely. Respondents identified NHS Athens accounts as providing a limited range of journals with practical difficulties in access with frequent trust changes. We have identified a need for improved information about resource availability and an unmet desire for easy online access to core journals.